Nutritional evaluation of stage 5 chronic kidney disease patients on dialysis - Piratelli, Cynthia Mauro; Telarolli Junior, Rodolpho (São Paulo Medical Journal, 2012)
CONTEXT AND OBJECTIVE: Patients with chronic kidney failure undergoing dialysis have high prevalence of protein-energy malnutrition. There is still no uniform method for assessing these patients’ nutritional status. It is recommended that a set of subjective and objective methods should be applied so that an adequate nutritional diagnosis can be reached. The aim of this study was to evaluate the nutritional profile of patients undergoing hemodialysis. DESIGN AND SETTING: Cross-sectional study conducted in the Dialysis Treatment Unit, Araraquara, São Paulo, Brazil, in 2008. METHODS: Anthropometric and biochemical indicators were characterized for 48 patients who also gave responses to the modified Subjective Global Assessment questionnaire (SGAm), and possible correlations between these indicators were investigated. RESULTS: The frequency of moderate or severe malnutrition ranged from 22% to 54%, according to the parameter used. Regarding the patients’ conformity with the ideal weight, 29% of them weighed less than 75% of the ideal, and thus were classified as having moderate or severe malnutrition. The most significant correlations were observed between body mass index (BMI) and the idealness of triceps skinfold (TSF), upper arm circumference (UAC) and upper arm muscle circumference (UAMC); and between SGAm and the idealness of UAC and UAMC. CONCLUSION: The frequency of malnutrition showed great variability among the patients, according to the evaluation criterion chosen. Routine nutritional monitoring and validation of methods for assessing body composition among such patients are extremely important for diagnosing malnutrition early on, thus preventing complications and reducing the morbidity and mortality rates in this population.